2017
DOI: 10.1111/1750-3841.13801
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Flavor of Traditional Soup Made by Stewing Chinese Yellow‐Feather Chickens

Abstract: The traditional recipe for Chinese chicken soup creates a popular taste of particular umami and aroma. The present study investigated the effects of stewing time (1, 2, and 3 h) on the principal taste-active and volatile compounds and the overall flavor profile of traditional Chinese chicken soup by measuring the contents of free amino acids (FAAs), 5'-nucleotides, minerals and volatile compounds and by evaluating the taste and aroma profiles using an electronic nose, an electronic tongue and a human panel. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 52 publications
5
88
1
Order By: Relevance
“…However, our team has reported that FAAs, 5ʹ-nucleotides, and minerals in Chinese yellow-feathered chicken broth increase remarkably with increased stewing time. [7] Similar results are reported by other authors. [12,13] These FAAs, 5ʹ-nucleotides, and minerals migrate from the chicken meat into the broth.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…However, our team has reported that FAAs, 5ʹ-nucleotides, and minerals in Chinese yellow-feathered chicken broth increase remarkably with increased stewing time. [7] Similar results are reported by other authors. [12,13] These FAAs, 5ʹ-nucleotides, and minerals migrate from the chicken meat into the broth.…”
Section: Introductionsupporting
confidence: 88%
“…[32] The decrease in the IMP in the chicken meat during stewing were consistent with results in goat meat after cooking [33] and was accompanied by a remarkable increase in the IMP content in the chicken broth. [7] Rotola-Pukkila et al [11] have reported that IMP in pork meat remained constant after cooking at 80°C for 120 min. This discrepancy could be due to differences in the intensity of the stewing.…”
Section: Changes In Faa Content With Different Stewing Timesmentioning
confidence: 97%
See 3 more Smart Citations